Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT. Alam Indah Property di Jakarta - Mohammad Amas Lahat; Rosento Sento; Amas Sari Marthanti (Peneliti.net, 2020)
This study aims to determine the effect of price and service quality on customer satisfaction at PT. Alam Indah Property in Jakarta. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, price has a significant effect on customer satisfaction by 40.9%, hypothesis testing obtained t count> t table or (8,320> 1,661). Service quality has a significant effect on customer satisfaction by 42.1%, hypothesis testing obtained t count> t table or (7.551> 1.661). Price and service quality simultaneously have a significant effect on customer satisfaction with the regression equation Y = 10.311 + 0.406X1 + 0.345X2 and the contribution of the effect is 50.6%, the hypothesis test obtained F count> F table or (47.631> 2,700).